Science In An Exponential World - Szalay, Alex; Gray, Jim (Nature, 2006)
Scientists are trained early to keep careful records in their laboratory notebooks — recording both experimental procedures and observations, so that they can analyse their results and so that others can replicate what they have done. Galileo did it, Mendel did it, Darwin did it, and we are supposed to do it.